The effect of a 6 Fr catheter in women: Are they obstructive? - Richard, Patrick; Ordonez, Nydia Icaza; Tu, Le Mai (Canadian Urological Association Journal, 2013)
Objectives: Our objective was to evaluate the effect of a 6 Fr transurethral catheter on the uroflowmetry and to assess whether it potentially contributes to the bladder outlet obstruction (BOO) in women. Methods: We reviewed the charts of 1367 women who underwent an urodynamic study. We included patients with a non-invasive free-flow study (NIFFS) and pressure flow study (PFS) performed through a 6 Fr double lumen transurethral catheter. Results: In total, 120 women met the inclusion/exclusion criteria. Mean maximal flow rate (Qmax) was significantly higher (p < 0.001) in the NIFFS (27.2±11.1 mL/s) than in the PFS (19.3±10.6 mL/s). The mean difference between both Qmax was 7.9±12.0 mL/s. Of these women, 92.3% (24/26) with a Qmax <12 mL/s during PFS were found to have a Qmax ≥12 mL/s during the NIFFS. Ten of the 72 women with an available Pdet.Qmax were deemed to have a BOO according to the PFS and all of them had a Qmax >12 mL/s during the NIFFS. Of the 10 patients, only 2 reported obstructive symptoms. Conclusion: The presence of 6 Fr transurethral catheters alters the PFS and results in a significant reduction of the Qmax in patients who voided more than 250 mL. We believe that NIFFS should be performed in all patients before any urethral manipulation to lower a possible overdiagnosis of BOO and findings should always be correlated to clinical symptoms.